Updating the civil legislation of Ukraine in the field of intellectual property in the modern information society - Kokhanovska, Olena V.; Verbytska, Anastasiia O.; Kokhanovskyi, Veleonin O. (Linguistics and Culture Review, 2021)
The purpose of this study was to analyse and investigate the modifications of the development of intellectual property rights in modern realities, followed by the authors' proposals to improve its evolution and adaptability. According to the results of the study, the sphere of intellectual property currently differs not only in the implementation and protection of rights compared to the original approaches laid down by the developers of the current Civil Code and branch-related special legislation, but also in the change in the paradigm of creative activity in information networks. Based on the provisions of several European Union Directives, the authors concluded that legal regulation in the field of intellectual property in Ukraine should be based on the experience of EU countries and conventional legal constructions known to national legal science, and use the principles inherent in this field in the Civil Code of Ukraine, including method of regulation, functions, terminology, etc.